1998
DOI: 10.1006/qres.1997.1959
|View full text |Cite
|
Sign up to set email alerts
|

Black Mats, Spring-Fed Streams, and Late-Glacial-Age Recharge in the Southern Great Basin

Abstract: Black mats are prominent features of the late Pleistocene and Holocene stratigraphic record in the southern Great Basin. Faunal, geochemical, and sedimentological evidence shows that the black mats formed in several microenvironments related to spring discharge, ranging from wet meadows to shallow ponds. Small land snails such as Gastrocopta tappaniana and Vertigo berryi are the most common mollusk taxa present. Semiaquatic and aquatic taxa are less abundant and include Catinellids, Fossaria parva, Gyraulus pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 17 publications
(4 reference statements)
8
150
1
Order By: Relevance
“…22). However, a wetter middle Holocene is inconsistent with numerous studies that attest to a drier middle Holocene (Harding, 1965;Lindstrm, 1990;Benson et al, 1991;Thompson, 1992;Benson, 1994a;Benson et al, 1997;Quade et al, 1998;Grayson, 2000). In fact, ages of tree stumps submerged in Lake Tahoe (Fig.…”
Section: -3430 Cal Yr Bpmentioning
confidence: 74%
See 1 more Smart Citation
“…22). However, a wetter middle Holocene is inconsistent with numerous studies that attest to a drier middle Holocene (Harding, 1965;Lindstrm, 1990;Benson et al, 1991;Thompson, 1992;Benson, 1994a;Benson et al, 1997;Quade et al, 1998;Grayson, 2000). In fact, ages of tree stumps submerged in Lake Tahoe (Fig.…”
Section: -3430 Cal Yr Bpmentioning
confidence: 74%
“…For example, the decreasing abundance of harvest mice between 9200 and B3500 cal yr BP indicates a much drier climate than during the early and late Holocene (Grayson, 2000). Farther south in the Great Basin, black mats, formed by spring discharge to wet meadows and shallow ponds, are absent from 7250 to 2500 cal yr BP, also indicating a period of relative aridity (Quade et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This was preceded by the anathermal (10,000-7000 cal yr BP) and followed by the medithermal (4500 cal yr BP to present) intervals marked by generally cool and wet climatic conditions. Dry Middle Holocene conditions in the Great Basin are also suggested by decreased sedimentation rates in the Ruby Valley marshlands of western Nevada between 7700 and 5500 cal yr BP (Thompson, 1992), decreases in spring discharge indicated by the absence of black mats in the southern Great Basin between $7300 and 2500 cal yr BP (Quade et al, 1998), and changes in the distribution of xeric flora (Hansen, 1947;Bright, 1966;Byrne et al, 1979;Mehringer, 1985;Madsen and Rhode, 1990) and associated fauna (Grayson, 2000). Axelrod (1981) argued that xeric (dry) vegetation expanded into the San Francisco Bay area in the Early and Middle Holocene and Moratto et al (1978) identified several dry episodes in the Middle Holocene based on pollen records from California (Birman, 1964;Adam, 1967;Curry, 1969;Sercelj and Adam, 1975;Wood, 1975;Casteel et al, 1977) and correlated these with the bristlecone pine precipitation record from the White Mountains (LaMarche, 1973(LaMarche, , 1974Graumlich, 1996, 2000) indicating a significant dry episode between 6000 and 4800 cal yr BP.…”
Section: Associated Terrestrial Climate Changesmentioning
confidence: 99%
“…Three distinct cycles are present in the Middle Holocene with warming between 8200-6300 and 5800-3800 cal yr BP, punctuated by a cool interval from 6300 to 5800 cal yr BP. The coldest SSTs during (Kennett and Ingram, 1995b;Huesser and Sirocko, 1997;Kennett and Kennett, 2000); (2) Leonard Rockshelter pollen sequence (Byrne et al, 1979); (3) Ruby Valley pollen record (Thompson, 1992); (4) Archeological pollen sequences (Masters and Gallegos, 1997); (5) Late Holocene tree ring record, coastal Southern California (Larson and Michaelson, 1989); (6) Santa Rosa Island pollen sequence (Cole and Liu, 1994); (7) Union pollen spectra (Morgan et al, 1991); (8) Bristlecone pine tree ring record (LaMarche, 1973(LaMarche, , 1974Graumlich, 1996, 2000); (9) Lake Tahoe submerged tree stump record (Lindstro¨m, 1990); (10) Southern Great Basin black mat records (Quade et al, 1998); (11) Owens Lake (Benson et al, 2002); (12) Pyramid Lake (Benson et al, 2002); (13) Tulare Lake geomorphology and pollen records (Negrini et al, 2006); (14) Buena Vista Lake and Elk Hills geomorphology (Culleton et al, 2005).…”
Section: Santa Barbara Basin Paleoenvironmental Recordmentioning
confidence: 99%
“…Quade et al (1998) and Pigati et al (2014) showed that the so-called "black mats" are common components of the deposits formed in wetlands. Interestingly, a "black, organic-rich layer in P14" was recorded by Dietze et al (2013) and ascribed to possibly "represent short-term sapropel deposition".…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%